Significance of Bcl-2、CD10、CD34 and CK15 expression in differentiating basal cell carcinoma from trichoepithelioma - Bing-mei LIU; Rong-gui XING; Li-jie XIA; Li LI; Han-wen ZHANG; Xue CHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To compare expression of Bcl-2, CD10, CD34 and CK15 in basal cell carcinoma(BCC) versus trichoepithelioma(TE), and to explore the significance of their expression in diagnosis and differential diagnosis of these two disorders. Methods: Paraffin-embedded tissue samples from 36 cases of BCC and 16 cases of TE were analyzed using immunohistochemistry of Bcl-2, CD10, CD34 and CK15. The expression of these biomarkers in tumor cells and tumor stroma was evaluated. Results: The positive staining rates of Bcl-2 (palisading arrangement) in BCC and TE were 0 and 68.75% respectively (P<0.01), while positive rates of CD10 in tumor cells of BCC and TE were 72.22% and 12.50% respectively (P<0.01). Moreover, positive rates of CD10 in stroma of BCC and TE were 2.78% and 62.50% respectively (P<0.01). Likewise, positive rates of CK15 in BCC and TE were 5.56% and 56.25%, respectively (P<0.01).However, positive rates of CD34 in BCC and TE were comparable (P>0.05). Sensitivities were CD10 (Tumour cells+) 72.22%>Bcl-2 (68.75%) >CD10 (Stromal+) 62.50%>CK15 (56.25%); Specificities were Bcl-2 (100%) >CD10 (Stromal+) 97.22%>CK15 (94.44%) >CD10 (Tumour cells+) 87.50%; Accuracies were Bcl-2 (90.38%) >CD10 (Stromal+) 86.54%>CK15 (82.69%) >CD10 (Tumour cells+) 65.38%; Positive predictive values were Bcl-2 (100%) >CD10 (Tumour cells+) 92.86%>CD10 (Stromal+) 90.91%>CK15 (81.82%); Negative predictive values were Bcl-2 (87.80%) >CD10 (Stromal+) 85.37%>CK15 (82.92%) >CD10 (Tumour cells+) 58.33%. Conclusions: Differentiated expression and distribution of Bcl-2, CD10 and CK15, but not CD34, in BCC and TE can benefit the differential diagnosis of these two tumors.